2012
DOI: 10.1039/c2em30545c
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime of combustion-generated environmentally persistent free radicals on Zn(ii)O and other transition metal oxides

Abstract: Previous studies indicated that Environmentally Persistent Free Radicals (EPFRs) are formed in the post-flame, cool zone of combustion. They result from the chemisorption of gas-phase products of incomplete combustion (particularly hydroxyl- and chlorine-substituted aromatics) on Cu(II)O, Fe(III)2O3, and Ni(II)O domains of particulate matter (fly ash or soot particles). This study reports our detailed laboratory investigation on the lifetime of EPFRs on Zn(II)O/silica surface. Similarly, as in the case of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 16 publications
8
101
0
Order By: Relevance
“…57,35 Previous studies have also shown that different metal speciations result in varying radical yields and changes to their persistency in ambient air. 14 Among the studied metals, copper and iron have shown the highest activity of EPFR formation, while zinc and nickel indicated extremely long EPFR lifetimes in ambient air (in months).…”
Section: Resultsmentioning
confidence: 99%
“…57,35 Previous studies have also shown that different metal speciations result in varying radical yields and changes to their persistency in ambient air. 14 Among the studied metals, copper and iron have shown the highest activity of EPFR formation, while zinc and nickel indicated extremely long EPFR lifetimes in ambient air (in months).…”
Section: Resultsmentioning
confidence: 99%
“…EPFRs were first proposed to form through the reduction of metal oxides by high-temperature exposure (above 150°C) to simple substituted aromatics, which electron and X-ray spectroscopy has shown to occur on CuO 12,13 and TiO 2 14 model systems. However, the longest-lived EPFR species observed to date are phenoxy radicals generated on ZnO 15 , which presents a significant challenge to the generic model of EPFR formation because it is usually not possible to create a Zn(I) oxidation state except under rare conditions 1620 . The extraordinary longevity of ZnO-generated EPFRs – lifetimes of 73 days in ambient conditions– suggests that Zn-containing PM may present an ongoing environmental hazard throughout remediation processes.…”
Section: Introductionmentioning
confidence: 99%
“…12,2123 For example, organic precursors chemisorbed on CuO and Fe 2 O 3 displayed one decay with the longest lifetime on CuO (74 min) resulting from phenol. 12,21 When phenol was chemisorbed on Ni and Zn, two subsequent decays were observed, and these decays were also the longest for each metal.…”
Section: Introductionmentioning
confidence: 99%
“…23 All decays from the model EPFR system implied phenoxyl radicals are the short-lived species, while semiquinone radicals are the long-lived species. 12,23 Semiquinone radicals, however, were suggested to decompose into phenoxyl radicals. 12,23 The differences in the aforementioned decay behavior resulted from metal speciation and, although not specifically mentioned here, the adsorbed organic precursor.…”
Section: Introductionmentioning
confidence: 99%